Dynamic Response of a Grid Connected Wind Farm with Different Types of Generators - Helmy Mohammed El_ Zoghby; S.M. Sharaf (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
For a wide areas wind farm, which composed of different zones of different wind turbines and different generators , this paper aims to simulate  a wind farm model that icludes  a wind turbine and three different  types of generators , which are three phase synchronous generator, three phase squirrel-cage induction generator and three phase doubly-fed induction generator ,these generators are the main machines that generally used in the field of wind energy generation.  All generators are connected in parallel at the point of common coupling (pcc)  and connected to the utility grid . This model is a simple representation of the actual  model of  zafarana  wind farm,  which is the biggest wind farm in Egypt and further to use it in different kinds of simulations, and display the difference in response among all generators, where all generators are  500 kw power rating , and subjected to the same operating conditions .After modeling the system, the transient response of the system will be studied and analyzed at different operating cases as:Case.1 constant wind speed operationCase.2 variable wind speed operationCase.3 sudden change in turbine mechanical powerCase.4 sudden change in wind speed.So this paper introduces a survey on the dynamic response of a large wind farm of different generators at different operating conditions  Keywords: modeling, synchronous generator, induction generator, wind farm, simulation model, transient analysis.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.175